MLP accumulation and remodelling in the infarcted rat heart. - Wilding, JR; Lygate, C; Davies, K; Neubauer, S; Clarke, K (2006)
Mutation of cytoskeletal protein genes results in abnormal protein function and causes cardiomyopathy. We hypothesised that cardiac levels of cytoskeletal proteins, such as dystrophin, desmin and muscle LIM protein (MLP), would be altered during remodelling caused by myocardial infarction (MI). We measured left-ventricular morphology, function and cytoskeletal protein levels 10 weeks after coronary artery ligation or sham operation in male Wistar rats. Two-dimensional echocardiography revealed significant impairment of systolic function and decreased ejection fraction in infarcted hearts compared with sham (47+/-5% versus 73+/-4%), commensurate with the development of heart failure. Western blotting was used to measure levels of beta-myosin heavy chain (beta-MyHC), a marker of hypertrophy, and levels of dystrophin, desmin, MLP, beta-tubulin, utrophin and syncoilin, using GAPDH for normalization. Relative to shams, beta-MyHC and MLP levels were increased 1.9-fold and 1.7-fold, respectively, in infarcted rat hearts, whereas the levels of other cytoskeletal proteins were unchanged. Both MLP and desmin protein levels correlated negatively with ejection fraction, with the strongest relation between MLP and ejection fraction (r=-0.95, n=13, p<0.0001). This work suggests that MLP may play an important compensatory role in cardiac remodelling following MI.